New frontiers in the treatment of comorbid cardiovascular disease in chronic obstructive pulmonary disease. (12th April 2019) - Brassington, Kurt; Selemidis, Stavros; Bozinovski, Steven; Vlahos, Ross
Abstract : Chronic obstructive pulmonary disease (COPD) is a disease characterised by persistent airflow limitation that is not fully reversible and is currently the fourth leading cause of death globally. It is now well established that cardiovascular-related comorbidities contribute to morbidity and mortality in COPD, with approximately 50% of deaths in COPD patients attributed to a cardiovascular event (e.g. myocardial infarction). Cardiovascular disease (CVD) and COPD share various risk factors including hypertension, sedentarism, smoking and poor diet but the underlying mechanisms have not been fully established. However, there is emerging and compelling experimental and clinical evidence to show that increased oxidative stress causes pulmonary inflammation and that the spill over of pro-inflammatory mediators from the lungs into the systemic circulation drives a persistent systemic inflammatory response that alters blood vessel structure, through vascular remodelling and arterial stiffness resulting in atherosclerosis. In addition, regulation of endothelial-derived vasoactive substances (e.g. nitric oxide (NO)), which control blood vessel tone are altered by oxidative damage of vascular endothelial cells, thus promoting vascular dysfunction, a key driver of CVD. In this review, the detrimental role of oxidative stress in COPD and comorbid CVD are discussed and we propose that targeting oxidant-dependent mechanisms represents a novel strategy in the treatment of COPD-associated CVD.